2022
DOI: 10.3389/fpls.2022.728167
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Exposure to Heat Stress Induces Phenotypic Resilience, and Genetic and Epigenetic Variations in Arabidopsis thaliana Offspring

Abstract: Plants are sedentary organisms that constantly sense changes in their environment and react to various environmental cues. On a short-time scale, plants respond through alterations in their physiology, and on a long-time scale, plants alter their development and pass on the memory of stress to the progeny. The latter is controlled genetically and epigenetically and allows the progeny to be primed for future stress encounters, thus increasing the likelihood of survival. The current study intended to explore the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 102 publications
(168 reference statements)
3
14
0
Order By: Relevance
“…Are the stochastic and deterministic route therefore two extremes of the same process? One argument holds against this: in A. thaliana , spontaneous epimutations mostly accumulate in the CG context (Becker et al, 2011; Denkena et al, 2021; Schmitz et al, 2011; van der Graaf et al, 2015) whereas environment-induced epialleles are most prominent in the CHG and/or CHH context (Annacondia et al, 2021; Lin et al, 2022; Wibowo et al, 2016; Yadav et al, 2022; Zhou et al, 2019). This supports the idea that the stochastic and deterministic route are, at least in the context of DNA methylation in plants, two fundamentally different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Are the stochastic and deterministic route therefore two extremes of the same process? One argument holds against this: in A. thaliana , spontaneous epimutations mostly accumulate in the CG context (Becker et al, 2011; Denkena et al, 2021; Schmitz et al, 2011; van der Graaf et al, 2015) whereas environment-induced epialleles are most prominent in the CHG and/or CHH context (Annacondia et al, 2021; Lin et al, 2022; Wibowo et al, 2016; Yadav et al, 2022; Zhou et al, 2019). This supports the idea that the stochastic and deterministic route are, at least in the context of DNA methylation in plants, two fundamentally different processes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the environmentally induced memories are relatively short and can exist only as somatic memories. Occasionally, somatic stress memory persists to the next generation, resulting in changes in genome stability, plant morphology and stress tolerance [ 4 , 5 , 6 , 7 ]. This process is known as intergenerational stress response.…”
Section: Introductionmentioning
confidence: 99%
“…This process is known as intergenerational stress response. And even less frequently, the memory of stress exposure is carried yet to another generation, without stress exposure, resulting in so called transgenerational stress response [ 7 , 8 ]. It has been well documented that a transgenerational memory can play a role in generating epigenetic variants, in the form of differential DNA methylation or/and histone modifications that can allow plants to exhibit a certain degree of tolerance to the environmental stresses and consequently lead to adaptation [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that transgenerational effects can influence offspring performance in many sexually propagated plants (Wang, 2005; Yadav et al, 2022; Zhang et al, 2013). However, the transgenerational effects may be more significant in asexually propagated plants (i.e., clonal plants) because they reproduce mainly via vegetative growth, so their offspring are more likely to encounter the same environment conditions as their parents (Hung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%